Character Transformation through Islamic Education: Literature Study of Al-Ghazali and Ibnu Miskawaih's Thoughts - Bunaya, Bunaya; Ilham Abdul Jalil (Penerbit Hellow Pustaka, 2024)
Education is an important component for every human being, especially in the realm of Islam. Basically, Islamic education directs humans towards a complete life or becoming a human being, with the hope of becoming one of the foundations of life in the afterlife, so that humans will know the nature of their existence with a religious mindset. This research aims to analyze the thoughts of Imam Al-Ghazali and Ibnu Miskawaih regarding Islamic Educational Thought. The research method used is library research (library study). Primary data used are books, journal articles, while secondary data is from websites, news and so on. The results of this research explain that Islamic education is human education consisting of body and spirit which has the potential to follow, where this will change due to educational patterns. In this way, education forms a religious human person or what is known as isabah al-khuluq al-syarif or a person who is noble in a substantial and essential way.